Physiotherapy Methods in the Era of Digital Transformation for Exercise Therapy to Reduce Myofascial Trigger Point Syndrome Pain in Rental Workers (International Forum of Researchers and Lecturers, 2024)
Prolonged computer typing can lead to chronic trauma, resulting in Myofascial Trigger Point Syndrome (MTrPs). MTrPs is an inflammatory condition of the muscle fascia, characterized by pain described as stabbing, burning, throbbing, cutting, and aching in the loose connective tissue surrounding the muscles. This condition often affects the upper extremity muscles, most commonly the Upper Trapezius. One physiotherapy method used to address MTrPs is exercise therapy with the auto stretching technique. This study aimed to investigate the effect of physiotherapy in the digital era on the delivery of exercise therapy to reduce MTrPs pain in rental workers. This study employed a quasi-experimental design with a Pre and Post Test With Control Group Design. Purposive sampling was used to recruit 16 participants. Auto stretching exercises were performed twice daily for 25 days. Pain was measured using the Visual Analogue Scale (VAS). Data normality was assessed using the Shapiro-Wilk test. Hypothesis testing was performed using the Paired Sample T-test, and the Independent T-test was used to compare groups. The results showed a significant reduction in MTrPs pain in rental workers (p = 0.0001; p < 0.05). This indicates that physiotherapy delivered through digital platforms, incorporating exercise therapy with auto stretching, can effectively reduce MTrPs pain in rental workers.